The Influence of Social Media Marketing and Viral Marketing on BrandLoyalty and Purchase Intention among Generation Z in the Digital Era(A Study on Daviena Product Users in TikTok Shop E-Commerce) - ervina; M. Sulhan (CV. Satria Jaya, 2025)
Ervina, a student of the Business Administration Study Program at Yudharta University Pasuruan,conducted a study in July 2025 entitled